Application of a flexible membrane to DEM modelling of axisymmetric triaxial compression tests on sands. (31st August 2018) - Lu, Ye; Li, Xiaojiao; Wang, Yuelin
Abstract: An innovative flexible membrane algorithm was developed and applied to the 3-D DEM modelling of axisymmetric triaxial compression tests on sands. This proposed flexible membrane was made of simply packed single spheres. The vertical and side extensions of the membrane were bounded by a series of boundary walls. These measures equipped the membrane with enough flexibility to contain local deformations of the cylindrical specimen which was comprised of un-bonded particles. With the application of the flexible membrane, the specimens failed with bulging shapes which were typical of axisymmetric triaxial tests. A comprehensive parametric sensitivity study indicated that the normal stiffness and particle size of the membrane spheres had limited influence on the test results, while the shear stiffness of the membrane spheres substantially enhanced the residual strength of the specimen. To examine the effectiveness of the flexible membrane algorithm, the numerical specimen was characterised on the macroscopic, mesoscopic and microscopic scales. The stress and strain response of the specimen well matched the laboratory test, and the volumetric strain presented apparent contraction and expansion stage. More importantly, the characterisation on the local void ratio clearly indicated the flexible membrane enabled full development of strain localisation inside the specimen.